2023
DOI: 10.1177/21501351221122971
|View full text |Cite
|
Sign up to set email alerts
|

Defining Expectations for Infants With Hypoplastic Left Heart Syndrome Who Survive Initial Surgical Palliation

Abstract: Background Overall one-year non-mortality outcomes for surgically palliated hypoplastic left heart syndrome (HLHS) patients remain understudied. Using the metric Days Alive and Outside of Hospital (DAOH), the present study sought to characterize expectations for surgically palliated patients’ first year of life. Methods The Pediatric Health Information System database was used to identify by ICD-10 code all HLHS patients who underwent surgical palliation (Norwood/hybrid and/or heart transplantation [HTx]) duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…While other studies have focused on characterising the number of days alive and out of hospital within 30 days of operation or in the first year of life for hypoplastic left heart syndrome patients, there are few studies that have quantified the number of days alive and out of hospital for multiple single-ventricle subgroups. [11][12][13] Overall median number of days alive and out of hospital in the first year of life for patients with a single-ventricle diagnosis was 278 days.…”
Section: Discussionmentioning
confidence: 99%
“…While other studies have focused on characterising the number of days alive and out of hospital within 30 days of operation or in the first year of life for hypoplastic left heart syndrome patients, there are few studies that have quantified the number of days alive and out of hospital for multiple single-ventricle subgroups. [11][12][13] Overall median number of days alive and out of hospital in the first year of life for patients with a single-ventricle diagnosis was 278 days.…”
Section: Discussionmentioning
confidence: 99%
“…The authors performed multivariate analysis and found that preterm birth, presence of chromosomal abnormality, nonwhite race, and heart transplant as index operation were factors independently associated with lower-quartile DAOH. 21 Taken together, these data may be used to inform resource allocation, clinician index of suspicion for complications, and preoperative hemodynamic optimization. For instance, a child with a low probability of achieving the Glenn TO due to nonmodifiable risk factors such as an anatomic diagnosis of HLHS with moderate tricuspid regurgitation may be allocated more intensive care resources.…”
Section: Commentmentioning
confidence: 99%